2021
DOI: 10.2196/29001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Behavioral and Psychological Symptoms of Dementia: Prospective Observational Study Using Actigraphy

Abstract: Background Although disclosing the predictors of different behavioral and psychological symptoms of dementia (BPSD) is the first step in developing person-centered interventions, current understanding is limited, as it considers BPSD as a homogenous construct. This fails to account for their heterogeneity and hinders development of interventions that address the underlying causes of the target BPSD subsyndromes. Moreover, understanding the influence of proximal factors—circadian rhythm–related fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 70 publications
(92 reference statements)
2
11
0
Order By: Relevance
“…Previous studies that have used diaries to daily assess NPS in dementia suggested a rather erratic nature of NPS. [16][17][18] This is in line with the growing body of evidence emphasizing the role of proximal causes of NPS including psychosocial factors (e.g., caregiver burden, caregiver communication style), environmental factors (e.g., light, temperature), and somatic conditions (e.g., pain, thirst). 17,19 Alternatively, the irregular course of NPI scores could also arise from methodologic issues related to the NPI.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies that have used diaries to daily assess NPS in dementia suggested a rather erratic nature of NPS. [16][17][18] This is in line with the growing body of evidence emphasizing the role of proximal causes of NPS including psychosocial factors (e.g., caregiver burden, caregiver communication style), environmental factors (e.g., light, temperature), and somatic conditions (e.g., pain, thirst). 17,19 Alternatively, the irregular course of NPI scores could also arise from methodologic issues related to the NPI.…”
Section: Discussionsupporting
confidence: 58%
“…[16][17][18] This is in line with the growing body of evidence emphasizing the role of proximal causes of NPS including psychosocial factors (e.g., caregiver burden, caregiver communication style), environmental factors (e.g., light, temperature), and somatic conditions (e.g., pain, thirst). 17,19 Alternatively, the irregular course of NPI scores could also arise from methodologic issues related to the NPI. Our finding that changes in NPI scores were unrelated to changes in caregiver burden could support this.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…4,5 Previous research indicates that gender, age, dementia severity, functional ability, comorbidities, pain, delirium, and the quality of staff-patient interactions can be associated with behavioral and psychological symptoms among individuals with dementia. [6][7][8][9] Additionally, when hospitalized, older adults with dementia may experience physical symptoms due to their acute illness or confusion related to their new hospital environment. This experience can increase behavioral and psychological symptoms of dementia, especially symptoms of aggression, motor disturbance, and sleep disturbance.…”
Section: Introduction 1| Hospitalized Older Adults and Behavioral/ Ps...mentioning
confidence: 99%
“…BPSD can be divided into four clusters: the hyperactivity cluster (agitation/aggression, euphoria, disinhibition, irritability, motor disturbance), the psychosis cluster (delusions, hallucinations), the mood lability cluster (depression/dysphoria, anxiety), and the instinctual cluster (appetite disturbance, sleep disturbance, apathy) 4,5 . Previous research indicates that gender, age, dementia severity, functional ability, comorbidities, pain, delirium, and the quality of staff‐patient interactions can be associated with behavioral and psychological symptoms among individuals with dementia 6–9 . Additionally, when hospitalized, older adults with dementia may experience physical symptoms due to their acute illness or confusion related to their new hospital environment.…”
Section: Introductionmentioning
confidence: 99%